Pandangan Fikh Siyasah Terhadap Larangan Rangkap Jabatan Wakil Menteri Dalam Pemerintahan Indonesia - Anggia Putri Syarani; Helena Syifa NST; Risky Azhari Selian; Cindy Aulia Rahma Batu Bara; Adrian Riyoeda Z.DS (Tabayyun : Journal Of Islamic Studies, 2023)
As a country with a majority Muslim population, Indonesia faces unique challenges in harmonizing the principles of Siyasah Fiqh with a secular government system. Efforts to understand and adapt Islamic principles to government policies are an important step in achieving this harmonization. Comparison with practices in other Muslim countries can provide additional insight into the suitability and sustainability of the policy of prohibiting multiple positions in Indonesia. Indonesia's government system, which adheres to a "presidential system," places power in the hands of the president. In this context, the prohibition on holding concurrent positions as Deputy Minister is regulated by Law Number 39 of 2008. This prohibition aims to ensure clear focus and responsibilities for the Deputy Minister, in accordance with the principles of Siyasah Fiqh. Juridical-normative legal research methods are used in this analysis, with emphasis on relevant literature. This research is descriptive and exploratory in nature, discussing aspects such as legislative politics, foreign policy, monetary politics, war politics and tactics. From the perspective of Siyasah Fiqh, the prohibition on holding multiple positions can be understood as implementing the principles of justice, transparency and accountability in government governance. These principles encourage the placement of officials based on competency and specialization, avoiding conflicts of interest, and ensuring efficient performance.